Oil and Gas Journal Databook (Penn Well Publishing Company TulsaUS, 1987)
Gives reports and surveys on pertinent issues in the worldwide petroleum industry. Reviews assets of major oil companies, outlines crude oil assays by country and gives results of worldwide petrochemical surveys. Discusses investment, construction, drilling, refining, and production in the worldwide oil industry. Reviews market situations, makes market forecasts and discusses other economic aspects of the worldwide oil industry.
IDS